Speculative designs: towards a social music - Ouzounian, G; Haworth, C; Bennett, P (Michigan Publishing, 2017)
This paper introduces a collaborative research project in which the authors explored the possibilities of music making using social media. We aimed for this music to reflect the various genres born of social media, for example the selfie, the tweet, the emoticon. Our research was therefore propelled by questions like “what might a musical selfie sound like?” and “how might an audio emoticon extend the language of online communication”? This project explored the potential of speculative design, or “design fictions”, in the creation of new musical interfaces. Overall, the project revealed the vast potential for new kinds of music making in today’s socially networked world.